G233(P) "Frequent flyers" in A and E and Urgent Care Centres – sociodemographic and practice characteristics of preschoolers who attend 4 or more times in a year. (27th April 2016) - Lim, V; Poots, A; Greenfield, G; Hiles, S; Mackenzie, G; Blair, M
Abstract : Background: Unscheduled attendances are increasing annually in preschool children under 5 years of age in England. Despite research in adult settings on recurrent attenders, there is limited UK data in pre-schoolers. Nationally, this is one of the largest population groups attending emergency and urgent care facilities. Further characterisation of socio-demographic, GP and clinical characteristics may identify a potential group suitable for intervention. We hypothesised that small and very; arge practices might have increased risk of PRA. Aims: To describe the socio-demographic and general practice factors of under-5 patients who attend an A&E and/or UCC in a large metropolitan DGH. Which socio-demographic factors are predictive of being a paediatric recurrent attender (PRA ) presenting with ≥4 ED visits? Does GP practice size have an influence on ED use? Methods: Retrospective study using a dataset of emergency attendances from 01 October 2013 to 30 September 2014. PRA is defined as a child younger than 5, with ≥4 unscheduled ED visits during the year. Descriptive statistics, univariate analyses and logistic regression techniques were used to analyse the characteristics of the study population. Deprivation measures included IMD and IDACI. Stata software was used to analyse the data. Results: During the study period, there were 16, 220 attendances by 9770 individual patients. 7.8% of patients accounted for 20.7% of visits. The distribution is shown in Table 1 . The following factors were found to be significantly predictive (p < 0.05) of being a repeat attender; male, infant, Asian ethnicity, of medium deprivation level, having a respiratory illness, and visiting EDs between 8pm and 8am. GP list size did not significantly affect the frequency of ED attendances. Limitations include suboptimal clinical coding and lack of data on GP: child patient ratios. Conclusion: This is the first study to combine both A and E and UCC data in a single locality. Children under five who attend 4 or more times in a year are more likely to be Asian infants from medium deprivation households, with a respiratory illness and attending out of hours. Clinical characterisation from more detailed notes review aims to identify those who might benefit from specialist community nursing support and educational intervention. We are currently interviewing parents in these groups to better understand motivations for attendance.